Antibody Levels against Newcastle Disease Virus, Infectious Bursal Disease Virus and Avian Influenza Virus in Rural Chickens in Viet Nam - Vui, Tran Quang; Lohr, J.E.; Kyule, M.N.; Zessin, K.-H.; Baumann, M.P.O. (International Journal of Poultry Science, 2002)
A serological survey on the prevalence of antibodies to Newcastle Disease (ND) virus, Infectious Bursal disease (IBD) virus and Avian Influenza (AI) virus was carried out in two communes of the Hue District, Middle Viet Nam. The villages in each commune and the households in each village included approximately 10% scavenging and 20% backyard chickens. The main objectives were to determine the prevalence of antibodies against ND virus at different seasons of the year, the prevalence of antibodies against IBD and AI virus, and a comparison of the situation of ND, IBD and AI in scavenging and backyard chickens. The results showed that there was no statistically significant difference in NDV titres between the seasons and between ND vaccinated and unvaccinated birds but there was a significant difference between the unvaccinated scavenging (33.9%) and the unvaccinated backyard birds (21.6%). Both ND vaccinated and unvaccinated birds in the 2- <6 months-old groups had a significantly lower NDV antibody titre than the > 6 month-old age group. There was no overt correlation between NDV-HI- and IBDV-ELISA titres. A statistical analysis was precluded due to inadequate data sets. There were 5 reactors in the AI-ELISA but they were negative in the HI test with H5 and H7 HA antigens. This study showed that in the selected chicken population the level of protection of vaccinated birds was unsatisfactory. It further showed that there was no seasonal difference between rainy and dry season, that IBDV existed but did not appear to be associated with NDV. There were no specific antibodies against the H5/H7 subtypes of AIV.